BEFORE AND DURING THE OUTBREAK: PREREQUISITES FOR THE HIGH COVID-19 MORTALITY RATE IN BULGARIA. EMPIRICAL INSIGHTS FROM SHARE DATA - Tosheva, Ekaterina; Yordanova, Gabriela; Lyubenova Markova, Ekaterina (Revista Inclusiones, 2021)
The first wave of Covid-19 (March-June 2020) did not hit Bulgaria to the same extent as it did other countries in Europe (Italy, Spain, Belgium, United Kingdom). The severe second wave of the pandemic in Bulgaria was in November-December 2020, with a third wave in March-April 2021, but Bulgaria had the second highest case mortality rate in Europe. The aim of this article is to analyse the empirical insights into the health expectancy and self-rated health of Bulgarians aged 50+ before and during the outbreak, which need to be taken into account as one of the important factors contributing to the high mortality rate of Covid-19. The analysis is based on SHARE wave 7 and the SHARE corona survey, conducted in July-August 2020. The data analysis results indicate that a significant share of Bulgarians aged 50 and over suffer from conditions considered high-risk for Covid19. A steady tendency to overestimate personal health can be observed even before the pandemic. The general health attitudes of elderly Bulgarians have not changed much. The overestimation of personal health, despite the presence of more than 2 chronic conditions, regular medication, combined with non-attendance of preventive examinations, dangerous habits and physical immobility increase the risk of acute viral diseases. The deteriorating health status of the elderly in Bulgaria appears to be a strategic risk factor in the case of an epidemic, which is confirmed by the Covid-19 crisis outcomes. In spite of the problems in the Bulgarian health system as a whole, personal attitudes towards health should be prioritized by public measures and policies, along with promoting an improvement in health culture, physical activity and preventive medical examinations.